Copyright Protection of Video Game Characters in Indonesia: Unauthorized Modding, Derivative Works, And A Three-Tier Regulatory Framework - Fadhil Ahda Muhaiyaadden; Deizan Azriel Drahmasyfa; Farhan Gunawan; Ikhwan Aulia Fatahillah (Adagium: Jurnal Ilmiah Hukum, 2026)
The expansion of the video game industry in Indonesia has intensified modding as a form of digital creativity while also exposing uncertainty over the legal boundaries of copyright protection for game characters. This article examines the legal status of video game characters, the qualification of unauthorized modding under Indonesian copyright law, and the regulatory reconstruction required to address the resulting grey areas. The study employs normative legal research using statutory, conceptual, comparative, and case approaches. Its principal legal materials include Law Number 28 of 2014 on Copyright, digital-law instruments, derivative-work doctrine, end-user licence agreements, technological protection measures, and scholarship on modding practices. The analysis finds that modding involving adaptation, transformation, public distribution, commercialization, or circumvention of technological protection measures may engage the exclusive rights of copyright holders, while private, non-commercial and non-distributive modifications remain less clearly regulated. The article develops a three-tier regulatory framework combining risk-based legal classification, institutionalized community licensing, and proportionate platform accountability. This framework is intended to protect legitimate copyright interests without eliminating socially valuable forms of participatory digital creativity.